GENETIC RELATIONSHIPS AMONG 15 XANTHOCERAS SORBIFOLIUM CULTIVARS USING SSR MARKERS AND PHENOTYPIC TRAITS - Y. L. Wang; L. Z. Zhu; Y. Li (Journal of Animal and Plant Sciences, 2023)
Xanthoceras sorbifolium is an important plants used for biofuel production and woody edible oil, which is cultivated in northern China.A number of cultivars have been selected by breeders, but little information has been available about their genetic relationships. The genetic diversity among 15 X. sorbifolium cultivars were evaluated combined using the eight fruit and ten seed phenotypic traits and twenty-six SSR loci. Significant variations in all phenotypic traits studied were observed. The mean coefficient of variation for phenotypic traits was 11.86%, and seed traits (12.09%)> fruit traits (11.58%). Based on the phenotypic traits 14 cultivars (one cultivar was fruitless) were clustered in three main groups and five subgroups, and reasonable utilization of each subgroup was suggested. According the twenty-six SSR loci 97 genotypes and 89 alleles were detected. The mean value of number of alleles, polymorphism information content, gene diversity and Shannon's information index (I) were 3.4231, 0.4375,0.3104 and 0.4760, respectively, indicating that the genetic diversity was medium among 15 cultivars of X. sorbifolium. Based on genetic distance, the 15 cultivars were classified into three main groups with a coefficient of variation of 0.64. These results can provide a groundwork for future cultivar identification and breeding programs in X. sorbifolium.
Keywords: X. sorbifolium; Genetic relationship; SSR markers; Morphological traits